Comparison of fitness performance among young football players on national and club level / Mohamad Afiq Ruslan - Ruslan, Mohamad Afiq (Faculty of Sport Science and Recreation, 2015)
Soccer is the main sport that played around the country. However , fitness performance is one crucial factor in developing in football team. The Aim of this study was to evaluate and compare speed, agility and V02max performance soccer players who plays in national and club level among youth soccer players. Fourty (N=40) youth male soccer players was selected that consist two team, National Football Development Programme (NFDP) (N=20) and PKNS Fe (N=20). This study was conducted by measuring anthropometric data by using three fitness test that been conducted which are 30m speed, t test shuttle run and yo-yo endurance test. The anthropometric data consist the elements of age, height, weight, and body mass index (BM!). Results show that has significant different on speed which is (p<O.05). In the same way, another results showed that has significant different on agility (p<O.05) and significant different on prediction vo2max (p<O.05) between both team during on that level played. There are many factors that can be used to determine the performance of the football players. Therefore, at present, all factors should be considered on monitoring the performance of football players among young to make sure all the players can be successful and have good performance during the competition season and growth with successful fitness component